Tropical tree growth driven by dry-season climate variability - Zuidema, Pieter A. (2022)
We acknowledge financial support to the co-authors Peru ‘s CONCYTEC and World Bank (043-2019-FONDECYT-BM-INC.INV.) to J.G.I, among others.